Development and Performance Investigation of a Unique Dual-rotor Savonius-type Counter-rotating Wind Turbine - Didane, Djamal Hissein; Kudam, Do'arsherah; Zulkafli, Mohd Fadhli; Mohd, Sofian; Batcha, Mohd Faizal Mohideen; Khalid, Amir (International Journal of Integrated Engineering, 2021)
Wind power is sustainable and prevalent virtually all over the globe. However, the conversion efficiency of the conventional single-rotor wind turbine (SRWT) is still far from satisfactory. The dual-rotor counter-rotating concept is among the reliable techniques used to enhance the efficiency of a wind energy conversion device for its renowned effectiveness. This study aims to investigate the performance of a Savonius dual/twin-rotor system, particularly in low-speed wind conditions while employing the counter-rotating technique. The evaluation of this technique is presented in terms of aerodynamic characteristics, including the power and torque coefficients. The results have shown that the new concept was able to improve the performance of the system extensively and was capable of operating in a lower wind speed condition. Compared to a single-rotor system, an additional 42% more torque was possible owing to the existence of a second rotor in the new system. The results have also revealed that the conversion efficiency of the system has been enhanced substantially. A corresponding average power coefficient of up to 28% was achieved. The present technique is thought to be promising for wind energy conversion systems, including sites with poor wind conditions.